Association of Premedication before Blood Transfusion with Transfusion Reactions in Mohammad Hoesin Hospital Palembang (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Premedication before blood transfusion is frequently used in clinical settings, albeit its effectiveness has not been shown. Premedication is used to stop transfusion-related fever and allergy. Unwanted or unanticipated consequences connected to the administration of unstable blood products are known as transfusion reactions. AIMS:  The aim of this study is to find out the association of premedication before blood transfusion with transfusion reactions. METHOD: This study is an observational analytic study with cross-sectional design, the data obtained from Mohammad Hoesin Hospital Palembang from January 1st, 2020 to December 31st, 2021. RESULT:  43 patients out of 73 samples did not receive premedication before the transfusion procedure, 8 patients (18.6%) experienced transfusion reactions, and 35 patients (81.4%) did not. 35 patients who received premedication, 2 patients (5.7%) experienced transfusion reactions, and 33 patients (94.3%) did not. The incidence of transfusion reactions at Mohammad Hoesin Hospital Palembang in the 2020–2021 period was not significantly associated with pre-transfusion premedication (p = 0.171). It is also not associated with blood transfusion history (p = 0.426), blood components (p = 0.793), or gender (p = 1.000). CONCLUSION:  Based on this finding, there is no significant association between premedication before blood transfusion and the transfusion reactions during period of 2020-2021 at Mohammad Hoesin Hospital Palembang.